IMPLEMENTASI SUPERVISI AKADEMIK KEPALA MADRASAH DI MAN BINJAI - Azhar, Zul; Hasibuan, Syahril; Herlinawati, Herlinawati; Lony, Adrina (Hijri, 2024)
The implementation of academic supervision should be able to increase teacher competence in teaching so that learning becomes more efficient and student learning outcomes can improve. The madrasa head has a crucial role in implementing academic supervision in the madrasa environment. However, in its implementation, there are a number of problems that arise and have the potential to hamper the effectiveness of academic supervision. This research aims to examine how academic supervision is implemented at MAN Binjai and the problems that arise during its implementation. The research method used is a combined method, through questionnaire surveys to teachers, interviews with madrasa heads, as well as documentation studies of academic supervision instruments. The subjects of this research included the head of the madrasah and twenty selected from six classes. The research results show that academic supervision at MAN Binjai has been carried out well according to the stages of academic supervision, namely pre-observation, carrying out observations, analyzing observation results, and providing feedback to teachers. The impacts felt by teachers include better preparation of Teaching Modules and RPPs as well as increased work motivation. Obstacles faced include schedule changes due to sudden agendas and the tendency to only copy teaching modules and lesson plans that existed in the previous academic year